2009
DOI: 10.1007/s12010-008-8519-2
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Kinetic Parameters in the Biosorption of Cr (VI) on Immobilized Bacillus cereus M1 16 in a Continuous Packed Bed Column Reactor

Abstract: Due to technological advancement, environment suffers from untreated toxic heavy metal bearing effluent coming from different industries. Chromium (VI) is one of those heavy metals having adverse impact on ecological balance, human, and plant health because of its carcinogenic properties. Biosorption is presented as an alternative to traditional technologies which are costly and inefficient for treatment of industrial wastes containing low amount of heavy metals. In this study, bioremediation of Cr (VI) ions b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 26 publications
(14 reference statements)
1
8
0
Order By: Relevance
“…At 367 mg l −1 of Pb(II), the breakthrough time was~40 min; however, it was~280-290 min when Pb(II) concentration was 79 mg l −1 . Packed column study for the removal of Cr(VI) using B. cereus, a bacterial biosorbent, also made similar observations [85]. Both the breakthrough and saturation time were longer at lower influent concentration of Cr(VI), and shorter at higher influent concentration.…”
Section: Concentration Of Metal Ion In Influentsupporting
confidence: 57%
See 2 more Smart Citations
“…At 367 mg l −1 of Pb(II), the breakthrough time was~40 min; however, it was~280-290 min when Pb(II) concentration was 79 mg l −1 . Packed column study for the removal of Cr(VI) using B. cereus, a bacterial biosorbent, also made similar observations [85]. Both the breakthrough and saturation time were longer at lower influent concentration of Cr(VI), and shorter at higher influent concentration.…”
Section: Concentration Of Metal Ion In Influentsupporting
confidence: 57%
“…This fact is also supported in the course of finding a flatter shape of breakthrough curve at high flow rate [54]. However, in the case of Cr(VI) sorption by Bacillus cereus packed column, Maiti et al [85] have demonstrated a steep breakthrough curve for high flow rate. Nonetheless, when the flow rate is very high, the column requires a longer period to reach saturation after attaining breakthrough point [68,128].…”
Section: Parameters Affecting Breakthrough Curvementioning
confidence: 71%
See 1 more Smart Citation
“…A great volume of work exists on the chromium reduction capacities of various organisms (e.g., bacteria (5,7,8,(29)(30)(31)(32) algae (33), and fungi (2,34)). While the use of non-modified live bacteria for bioremediation efforts has been documented, Cr(VI) removal efforts often focus on use of acidified environments and/or acid treated biomass.…”
Section: Discussionmentioning
confidence: 99%
“…In aqueous solution Cr(VI) predominately exists as chromate ion 33 and easily penetrates into biological membranes and cause cellular damage by inducing oxidative stress 79,80 . If Cr(VI) is more than its permeable level (0.05 mg/L) in the domestic water supplies which was set by the US EPA and the European Union 81 , was causes severe diarrhea, ulcers, eye and skin irritation, kidney dysfunction and probably lung carcinoma by accumulating in living tissues throughout the food chain due to its non-biodegradable metallic nature 82,83 . It may also cause renal tubular necrosis, chronic ulceration and perforation of the nasal septum 84 .…”
Section: Introductionmentioning
confidence: 99%